EP.WE.46Stentolith as an uncommon complication of loss to follow up after endoscopic biliary stenting. (28th October 2021) - Ng, Sherwin; Lam, Mark; Gill, Nina; Shamali, Awad
Abstract: Introduction: Endoscopic biliary stenting is a common procedure, with indications from malignant obstruction to benign stone disease. We discuss a patient who re-presented after endoscopic stenting having been lost to follow up, with a large 'stentolith' requiring open CBD exploration. Case Presentation: A 56-year-old female presented in 2013 with obstructive jaundice and a 2-week history of abdominal pain. She was a smoker, but otherwise had no past medical, surgical, or relevant family history. After initial workup, ERCP with sphincterotomy and pigtail stent placement was performed with interval laparoscopic cholecystectomy in 2014. Post-operative follow up was not arranged, the patient subsequently re-presented in 2020 with fatigue. MRCP confirmed a proximal CBD stone and linear artefact. Open exploration facilitated removal of the stone-stent complex. Discussion: Complications of stenting include cholangitis, stent occlusion and migration. Stenting for failed biliary stone extraction is considered a temporary measure, with removal or exchange at three months. However, patients may be lost to follow up and return with non-specific symptoms. A rare cause is de novo formation of a gallstone calculus encasing the stent, a phenomenon termed "stentolith". Proposed pathophysiology is through promotion of bacterial proliferation by the stent, with biofilm formation and calcium bilirubinate precipitation. Variation in formation has been described, with plastic stents developing circumferential stones, due to potential space between the wall and stent. Conclusion: This highlights the importance of robust inter-disciplinary working, careful patient follow up and implementation of a mandatory registry at all hospitals for stented patients.